A nonlinear poroelastic theory of solid tumors with glycosaminoglycan swelling. (21st November 2017) - Xue, Shi-Lei; Lin, Shao-Zhen; Li, Bo; Feng, Xi-Qiao
Highlights: A nonlinear poroelastic theory describing the chemo-mechanical behavior of tumors is proposed. We show that the mechanical resistance of tumors is primarily attributed to the GAG swelling. The contribution of the movement of interstitial fluid and the permeability on tumors' time-dependent behavior is analyzed. The theoretical results show good agreement with relevant experimental observations. Abstract: Mechanics plays a crucial role in the growth, development, and therapeutics of tumors. In this paper, a nonlinear poroelastic theory is established to describe the mechanical behaviors of solid tumors. The free-swollen state of a tumor is chosen as the reference state, which enables us to avoid pursuing a dry and stress-free state that is hard to achieve for living tissues. Our results reveal that the compression resistance of a tumor is primarily attributed to glycosaminoglycan (GAG) swelling, and the compactness of cell aggregates is found to affect tumor consolidation. Over-expressed GAGs and dense cell aggregates can stiffen the tumor, a remodeling mechanism that makes the tumor with higher elastic modulus than its surrounding host tissues. Glycosaminoglycan chains also influence the transient mechanical response of the tumor by modulating the tissue permeability. The theoretical results show good agreement with relevant experimental observations. This study may not only deepen our understanding of tumorigenesis but also provide cues for developing novel anticancer strategies.